Grid-Integrated Bidirectional EV Charger for G2V-V2G Mode with Optimized Power Quality - Sachan S.; Keshari R.K.; Swarnkar P. (My University, 2025)
The rapid expansion of the electric vehicle (EV) market has several prospects for expanding the use of clean energy in the automobile industry. In order to keep up with the surging interest in EVs, there has to be a concentrated effort to improve the charging infrastructure. This study describes a concept which integrates single-phase grid with bidirectional EV battery charger having G2V-V2G (Grid-to-Vehicle-Vehicle-to-Grid) capabilities. The 2-stage bidirectional EV charger system has been modeled in MATLAB Simulink to enhance the power quality. The simulation study showcased that a genetic algorithm (GA) optimized EV charger controller had a lower total harmonic distortion (THD) content in grid current when compared to EV charger that did not have an optimized controller. © 2023 IEEE.